Antioxidant Activity Test of Tomato Extract Face Mist (Solanum lycopersium L.) - Apsari, Anindya Hana; Rachma, Bashita Rizka; Yulianto, Susilo; Nugroho, Praptanti Sinung Adi (JSMARTech: Journal of Smart Bioprospecting and Technology, 2024)
Tomatoes contain compounds that act as natural antioxidants and are useful toward off free radicals. Tomatoes can be used as a basic ingredient in the development of facial cosmetics in the form of face mist. The purpose of this study was to determine the antioxidant activity of face mist tomato extract (Solanum lycopersicum L.). This study used quantitative methods with a descriptive research design. The organoleptic face mist has a yellow color with a distinctive oleum rosae aroma and is liquid. The homogeneity test results show all four homogeneous formulas. pH test results range from 4.71±0.005 to 5.68±0.015. The dry time test results were in the range of 2.39±0.015 – 3.12±0.015 minutes. The color test results on the face mist showed that it was positive for beta-carotene with a blue color. The IC50 value of face mist preparations at F0, F1, F2 and F3 was 208.488 ppm, 124.304 ppm, 73.683 ppm and 56.271 ppm, respectively. F0 face mist preparations are very weak antioxidants, F1 are moderate antioxidants, F2 and F3 are strong antioxidants. From this research can be concluded that the best formula to use F3.